The Influence of EMKM SAK on Transparency and Accountability of UMKM Financial Reports - Tina Susana Nora Afra; Cakti Indra Gunawan; Hendrik Suhendri (International Research & Development for Human Beings (IRDH), 2024)
The financial statements in this study are based on the Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM), which can be used to simplify the preparation of financial statements for business actors (UMKM) to make them more simplified and easier to understand for creditors, investors, and the government. This effort is expected to provide financial assistance or financing for UMKM (MSME). The purpose of this study is to determine the impact of the implementation of SAK EMKM on Accountability and Transparency in UMKM financial statements. This research method uses a quantitative method, with multiple regression analysis tools. Data collection uses primary data by distributing questionnaires to 150 respondents. The results of this study simultaneously explain the relationship between the variables studied with the Fcount>Ftable (3.743>0.006) so that it can be concluded that the entity's financial position report based on SAK EMKM, the entity's profit and loss report based on SAK EMKM, notes to the entity's financial statements based on SAK EMKM, socialization and information on SAK EMKM together (simultaneously) have an effect on the accountability and transparency of UMKM financial reports, while for the results of the determination coefficient (R2) of 0.0094 it can be concluded that the contribution of the independent variable has an effect on the dependent variable of 9.4% and the remaining 90.6% is influenced by other variables outside this model.